A framework for sustainable construction initiatives in Malaysia / Nur Hidayah Idris - Idris, Nur Hidayah (2014)
This research aims to propose a framework for sustainable construction initiatives in Malaysia. Extensive literature review on the development of sustainable construction initiatives in Singapore, Hong Kong and Japan indicated active utilisation. However,the green movement in Malaysia is in infancy where sustainable projects in Malaysia are mostly at the pioneer stage. Mixed methods of quantitative and qualitative research were adopted in this research in order to develop a framework for sustainable construction initiatives in Malaysia. Empirical data for quantitative research was collected via questionnaire survey and qualitative data was gathered via semistructured interviews. One hundred and fifty responses were received from developers in Malaysia and analysed by SPSS (Statistical Analysis for the Social Science). Quantitative finding shows that there are eleven impediments exist to implement sustainable construction in Malaysia. Further, the quantitative data was also analyse using relative importance index (RII) method to justify their ranked according to their important. Therefore, qualitative research was conducted in order to identify the most important impediments and the strategies to further implement sustainable construction in Malaysia. The establishment of the framework was drawn from the analyses and results of two stages of data collection, mainly via cross sectional survey and semi-structured interviews. The framework suggests that the government plays an important role to increase demand on sustainable project by giving fully support in cost and green product supplier in order to encourage the construction practitioner to build more sustainable projects in the future.